Synthsis and Structural Characterization of New Metal Complexes and Mixed Ligand Complexes of 2-N-(3, 4-DIHYDROXY BENZYLIDENE) BENZOTHIAZOLE - Abdul-Ghani, Ahlam; Majeed, R. (Iraqi Journal of Science, 2025)
The new Schiff base 2-N-(3,4-dihyroxy benzylidene) benzothiazole (H2L1) was prepeared from reaction of 2-aminobenzothiazol (2-ABT)and 3,4- dihdroxy benzaldehyde. Metal complexes of the new ligand with metal ions Co(II), Ni(II), Cu(II), Pd(II), Pt(IV), and Ru(III) were prepared by reacting H2L1. (2 mmole) with the metal ions (1mmole) in presence and absence of triethylamine (Et3N,2mmole) in ethanol . Mixed ligand complexes (ML’LI ) were synthesised by reacting H2LI and other ligands L’ acetylacetone, (acac). ethylene diamine (en), 2,2- bipyridyl (bipy), and the Schiff base HLII that has been already prepared from 2-ABT and salicylaldehyde, with metal ions and ET3N in a molar ratio of 1:1:1:2, respectively in ethanol. Structures of the new compounds were characterised by elemental and thermal analyses as well as i.r and u.v- visible spectra. The magnetic properties and electrical conductivities of metal complexes were also determined . Some complexes exhibted biological activities against two types of pathogenic bacteria.